Evaluation of biocontrol agents and fungicides against stem bleeding disease of coconut - Meena, B.; Ramjegathesh, R.; Ramyabharathi, S.A. (Journal of Plantation Crops, 2014)
Evaluation of biocontrol agents and fungicides against stem bleeding disease of coconut